Knowledge Management Systems Analysis and Planning for Employees Recruitment and Training - Abdillah, Leon A.; Purwanto, Tri A.; Agustini, Eka P. (Journal of Electrical, Electronics and Informatics; Vol 4 No 2 (2020): JEEI (August 2020)DO - 10.24843/JEEI.2020.v04.i02.p01, 2020)
The development of science in the era of globalization is happening so quickly. The ability of humans to develop a variety of science (knowledge) is getting better with the tacit and explicit knowledge. From this development both tacit and explicit knowledge can be combined and varied to a Knowledge Management System. PT SCF (Limited) Palembang branch is a company engaged in the field of inspection and certification services. The problem faced by this company is that the process and media for sharing and transferring knowledge between colleagues is still small and not yet entrenched. This condition makes the company less effective in terms of producing and disseminating knowledge to staff quickly and accurately. Documentation of daily activities and routines are not carried out in a planned and integrated manner. Each department carries out its own activities in its own way, for example storing documentation on a CD, as well as a piece of paper. So the authors are interested in analyzing and designing Web Knowledge Management System. The method used is the object analysis and design method. While the tools for modeling using Unified Modeling Language (UML). The results obtained are a prototype web Knowledge Management System (KMS) that can be a media of information and knowledge sharing related to employee acceptance and training